PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT SAHABAT DUA MUDA JAKARTA BARAT - Zahra Tunnisah; Maswarni (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of this study is to determine the effect of Work Discipline and Physical Work Environment on Employee Performance at PT. Sahabat Dua Muda, West Jakarta, both partially and simultaneously. This research uses a quantitative method. The population in this study consists of 70 respondents. The sampling technique uses a saturated sampling method, resulting in a total sample of 70 respondents. Data analysis techniques include validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study indicate that the effect of Work Discipline (X1) on Employee Performance (Y) is based on the regression equation Y = 39.398 + (-0.092) X1. The hypothesis test shows that the t-count < t-table (-0.933 < 1.997), meaning that H0₁ is accepted and Ha₁ is rejected. Therefore, there is no significant effect of work discipline on employee performance. The effect of Physical Work Environment (X2) on Employee Performance (Y) is based on the regression equation Y = 21.884 + 0.440X2. The hypothesis test shows that the t-count > t-table (7.694 > 1.997), indicating that H0₂ is rejected and Ha₂ is accepted. Thus, there is a significant effect of the physical work environment on employee performance. Simultaneously, the effect of Work Discipline (X1) and Physical Work Environment (X2) on Employee Performance (Y) is based on the regression equation Y = 22.417 + (-0.014)X1 + 0.439X2. The hypothesis test shows that the F-count > F-table (29.199 > 3.13), meaning that H0₃ is rejected and Ha₃ is accepted. Therefore, there is a significant simultaneous effect of work discipline and physical work environment on employee performance.